Optimum groundwater table depth and irrigation schedules for controlling soil salinity in Central Iraq - Qureshi, Asad Sarwar; Ahmad, Waqas; Ahmad, A.F.A. (Wiley, 2013)
Excessive irrigation and poor drainage conditions are the major factors contributing to rising groundwater tables and soil salinity in the irrigated areas of Central Iraq. Therefore calculations of precise irrigation requirements are necessary to optimize crop production and keep the groundwater table below the root zone to avoid soil salinization. In this study, the soil-water-atmosphere-plant (SWAP) model is used to determine optimal groundwater table depth and irrigation amounts for the study area. SWAP was calibrated using field data from the study area during the wheat and maize season of 2011-2012. The modelling results reveal that under current irrigation practices (600mm to wheat and 1000mm to maize), more than 30% water is lost as deep percolation. This causes a rise in the groundwater table and reduction in crop yields. The model simulations suggest that a groundwater table depth of 200 cm together with an irrigation application of 500mm to wheat and 600mm to maize will be the best combination to attain optimal yields. Therefore a drainage system in these areas should be installed to maintain groundwater table depth around 200 cm. Maintaining adeeper groundwater table will not be suitable as costs will increase and crop responses negligible. For long-term sustainability, rehabilitation of existing drainage systems to evacuate excessive salts from the root zone will be imperative.